Efficient CO2-Reducing Activity of NAD-Dependent Formate Dehydrogenase from Thiobacillus sp KNK65MA for Formate Production from CO2 Gas - Choe, Hyunjun; Joo, Jeong Chan; Cho, Dae Haeng; Kim, Min Hoo; Lee, Sang Hyun; Jung, Kwang Deog; Kim, Yong Hwan (PUBLIC LIBRARY SCIENCE, 2014)
NAD-dependent formate dehydrogenase (FDH) from Candida boidinii (CbFDH) has been widely used in various CO2 reduction systems but its practical applications are often impeded due to low CO2-reducing activity. In this study, we demonstrated superior CO2-reducing properties of FDH from Thiobacillus sp. KNK65MA (TsFDH) for production of formate from CO2 gas. To discover more efficient CO2-reducing FDHs than a reference enzyme e. CbFDH, five FDHs were selected with biochemical properties and then, their CO2-reducing activities were evaluated. All FDHs including CbFDH showed better CO2-reducing activities at acidic pHs than at neutral pHs and four FDHs were more active than CbFDH in the CO2 reduction reaction. In particular, the FDH from Thiobacillus sp. KNK65IVIA (TsFDH) exhibited the highest CO2-reducing activity and had a dramatic preference for the reduction reaction, i.e., a 84.2-fold higher ratio of CO2 reduction to formate oxidation in catalytic efficiency (k(cat)/K-B) compared to CbFDH. Formate was produced from CO2 gas using TsFDH and CbFDH, and TsFDH showed a 5.8-fold higher formate production rate than CbFDH. A sequence and structural comparison showed that FDHs with relatively high CO2-reducing activities had elongated N- and C-terminal loops. The experimental results demonstrate that TsFDH can be an alternative to CbFDH as a biocatalyst in CO2 reduction systems.
Keywords: CARBON-DIOXIDE; ESCHERICHIA-COLI; ELECTROCHEMICAL REGENERATION; NICOTINAMIDE COFACTORS; FORMIC-ACID; REDUCTION; GENE; CLONING; COMPLEX; PURIFICATION